Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/resp.12059
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of patient self‐report as a measure of inhaled asthma medication use

Abstract: Self-report is inaccurate in measuring actual use of inhaled asthma treatment with patients who underuse their maintenance therapy overreporting their use and those who overuse their therapy underreporting their use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 30 publications
2
43
1
Order By: Relevance
“…In accordance with previous studies [22], the present study showed that self-reporting, in general, is not a valid measure of actual adherence to ICS, although we observed that it seems to be more accurate during pregnancy than in non-pregnant women. This could be due to the women feeling responsible for more than their own health, and thus reporting more truthfully, or it could be a coincidence.…”
Section: Discussionsupporting
confidence: 76%
“…In accordance with previous studies [22], the present study showed that self-reporting, in general, is not a valid measure of actual adherence to ICS, although we observed that it seems to be more accurate during pregnancy than in non-pregnant women. This could be due to the women feeling responsible for more than their own health, and thus reporting more truthfully, or it could be a coincidence.…”
Section: Discussionsupporting
confidence: 76%
“…In Europe, the loss of productivity and work impairment due to asthma is estimated as EURO9.8 billion per year (ERS 2015). Poor adherence to maintenance inhaled corticosteroid therapy is a challenge for those treating patients with asthma, as parental reporting in children and self-reporting in adults have been shown to correlate poorly with actual use (Tashkin 1991;Bender 2000;Burgess 2011;Patel 2013). Prescription checks are also imprecise, merely representing the maximum that could have been taken.…”
Section: B a C K G R O U N D Description Of The Conditionmentioning
confidence: 99%
“…Electronic monitoring devices, initially termed "nebuliser chronologs", were first described in asthma clinical practice in the 1980s (Spector 1986). They were prone to technical problems (Gong 1988;Nides 1993), but since then have been more successfully used to monitor treatment usage (Gibson 1995;Foster 2012;Patel 2013). They make it possible to record medication usage and patterns of treatment.…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…Several studies have shown the level of ICS adherence to be dependent on the method of measuring, 52-54 but even when including only studies using CMA/medical possession ratio as a measure of ICS adherence, the average adherence has been shown to range from 22% 22 to 50%. 19 CMA is considered to be reliable way of measuring ICS adherence, as it does not involve patient self-reporting, which leads to overestimated adherence, 52 although clearly communicating a no-blame attitude highly improves the accuracy of self-reporting. 55 One of the major problems with assessing adherence as CMA is that we have no way of knowing if the patients take their medication after filling their prescriptions or if they use the correct inhalation techniques, and thus, actual adherence might be even lower than that calculated.…”
Section: Summary and Perspectivesmentioning
confidence: 99%